Green Composites Processing, Characterisation and Applications for Textiles - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology,, 2019)
This book highlights the processing, characterization and applications of various green composites. Composites are known for their unique properties, which are derived by combining two or more components. This yields properties such as greater strength and rigidity than that of the individual components, as well as reduced weight. To help achieve such outcomes, the book discusses the potential applications of hybrid bio-composites and sisal-fiber-reinforced epoxidized non-edible oil-based epoxy green composites.